Toshié : a story of village life in twentieth-century Japan - Partner, Simon, 1958- (History e-book project., 2004)
Sakaue Toshie was born on August 14, 1925, into a family of tenant farmers and day laborers in the hamlet of Kosugi. The world she entered was one of hard labor, poverty, dirt, disease, and frequent early death. By the 1970s, that rural world had changed almost beyond recognition.